Effect of sand fractions on sandy soil –peat mixture, and irrigation intervals, infiltration rate, bulk density and grass performance in play yard. - Aziz, Salahaddin Abdulqadir; Taha, Zhalla Yadgar; Rasheed, Ali Mohamad (Sulaimani Journal for Pure and Applied Sciences, 2017)
In sand-soil mixtures, the sand fractions mixture with peat is strongly influence the soil physical properties and the yield dry matter of turf grass in the sports field. This investigation involved to study effects of three sand fractions (0.05-1, 0.05-2 and 0.5-2) mm, depth of irrigation water (14, 18 and 22 mm) and compaction on some physical characteristics of sand-based media such ( bulk density, infiltration rate and dry matter yield of turf grass. Three different sand fractions in size of sand-soil mixtures and three depths of irrigation water were prepared in which the percentage of added sand to silty clay soil was 60% by the weight. A (30cm) layer of mixture underlined by a layer of (10cm) medium gravel and 5cm coarse sand is placed in the bottom of the containers of (40 cm) diameter and 50 cm height , then cultivated with Mediterranean grass (Cynodon dactylon) using sowing rate of (35 g m-2). The A factorial experiment was conducted using complete randomized design with three replicates. Mixtures were compacted daily for 60 days to simulate foot-traffic. The results showed that after compaction, sand fractions (0.05 –1) mm in comparing with other two replaced with (sand) fractions (0.05–2 and 0.5-2) mm, had adequate infiltration rate (6.20 cm hr-1) to retain any intensive rainfall and the yield dry matter of grass turf significantly increased in the same treatment. The infiltration rate decreased significantly with increasing water depletion in both uncompacted and compacted treatments. Infiltration rate was at rate (2.3 cm hr-1) with compaction and at the depletion of (22 mm) water depth. The results also revealed that the value of bulk density was (1.59 Mg m-3), which is higher, compared to their values in the sand (0.05-2 mm) and (0.05-1 mm) which were (1.47 Mg m-3) and (1.42 Mg m-3) at both uncompacted and compacted, respectively.
Keywords: bulk density infiltration rate sand fraction mixture compaction irrigation interval sport field turf grasses